Upaya Meningkatkan Motivasi Belajar Peserta Didik dalam Pembelajaran PJOK Melalui Permainan Hijau Hitam - Jamaluddin Imamy; Nanik Indahwati; Demy Ilmiawan (Journal of Creative Student Research, 2024)
The aim of this research is to determine the increase in student learning motivation in PJOK (Physical Education, Sports, and Health) through the Green-Black game. The method used in this research is the classroom action research (CAR) method. The research was divided into two cycles. From the data obtained in cycle 1, the average student learning motivation was 43.9%, and in cycle 2, it increased to 74.72%, showing an average increase of 30.82%. Thus, there was a significant increase in student learning motivation. This data also serves as evidence of the success of using the Green-Black game to improve student learning motivation in PJOK lessons..